Introduction to information technology - Turban, Efraim; Rainer, R. Kelly, Jr. 1949-; Potter, Richard E. (John Wiley & Sons, Inc, 2003)
This text is based on the fundamental premise that the major role of information technology (IT) is to support employees, regardless of their functional area (sales, marketing, accounting, HR) or level in the organization. It provides the tools that enable employees to better perform.